An International Study of Accounting Practices in Divisionalized Companies and Their Associations with Organizational Variables. - Scapens, Robert W.; Sale, J. Timothy (The Accounting Review, 1985)
ABSTRACT: The measurement of divisional performance is still a subject of some debate. Most accounting researchers appear to favor measures which either include an interest charge on capital employed or relate divisional income to its capital asset base, but some dissenters exist. Various measures are used in practice. The use of particular accounting methods is hypothesized to be influenced by organizational characteristics, such as the extent to which decision making authority has been delegated to divisional managers. An empirical study of associations between 12 variables reflecting accounting methods and the nature of divisional autonomy was undertaken from questionnaire surveys of large companies in the United States (U.S.) and the United Kingdom (U.K.), and the relationship between accounting methods and the nature of divisional autonomy in the two countries is examined. Many similarities were observed in the accounting methods used by the responding companies in the U.S. and the U.K. to evaluate divisional performance, analyze divisional capital expenditure proposals, and control authorized divisional capital expenditures. The major difference between the countries was the use of post-completion audits by more than twice as many U.S. companies (84.2 percent) as U.K. companies (36.3 percent). In both countries, the expected associations between accounting methods and divisional autonomy were not found. Further research is needed to explore the dynamics of accounting systems in divisionalized companies, such as longitudinal studies of individual companies.